2003
DOI: 10.1021/es020902v
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study of Hydrated Lime Reaction with HCl

Abstract: Hydrochloride (HCl) is an acidic pollutant present in the flue gas of most municipal or hazardous waste incinerators. Hydrated lime (Ca(OH)2) is often used as a dry sorbent for injection in a spray reactor to remove HCI. However, due to the short residence time encountered, this control method has generally been found to have low conversion efficiencies which results in the high lime usage and generates large amount of fly ash as solid wastes. A fundamental study was carried outto investigate the kinetics of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 17 publications
0
54
1
Order By: Relevance
“…It has been widely reported that the calcium-based sorbents with larger surface area and pore volume exhibit better HCl absorption behavior [37][38][39]. Gupta and Fan [51] found that sufficient surface area and pore volume benefited the gaseous diffusion and led to the rapid reaction kinetics of CaO-HCl.…”
Section: Microstructure Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It has been widely reported that the calcium-based sorbents with larger surface area and pore volume exhibit better HCl absorption behavior [37][38][39]. Gupta and Fan [51] found that sufficient surface area and pore volume benefited the gaseous diffusion and led to the rapid reaction kinetics of CaO-HCl.…”
Section: Microstructure Analysismentioning
confidence: 99%
“…The CO 2 capture capacity of the CaO/Ca 3 Al 2 O 6 sorbent prepared from carbide slag, Al(NO 3 ) 3 ·9H 2 O, and glycerin water solution by the combustion synthesis could achieve 1.8 times as high as that of the carbide slag after 50 cycles due to the more porous structure, larger surface area, and pore volume in the multiple cycles [29]. The calcium-based sorbent with more porous structure, larger surface area, and pore volume could achieve higher HCl absorption capacity [37][38][39]. Therefore, the CaO/Ca 3 Al 2 O 6 sorbent may be used to sequentially capture CO 2 and HCl from the flue gases of the biomass-fired and the RDFs-fired boilers.…”
Section: Introductionmentioning
confidence: 99%
“…Popular choices for H 2 S removal include the Ca- (Li et al, 2007), Fe- , Mn- (Bakker et al, 2003;Ko et al, 2005), Zn-based sorbent (Bu et al, 2008), and mixed metal oxide sorbent (Ko et al, 2007;Lou et al, 2009;Chang et al, 2012); those for HCl removal include the Ca- (Yan et al, 2003;Chin et al, 2005), Na-based sorbent (Nunokawa et al, 2008), and industrial catalyst mixed with multiple components (Dou et al, 2005). Due to the fact that a high percentage of the pollution emitted by coal gasification comes from sulfides, research activities focusing on desulfurization have been widely studied; while relatively little attention has been paid to dechlorination.…”
Section: Introductionmentioning
confidence: 99%
“…Popular candidates for desulfurization include Ca-based sorbent (Li et al, 2007), Fe-based sorbent (Ko et al, 2006), Mn-based sorbent (Bakker et al, 2003;Ko et al, 2005), Zn-based sorbent (Bu et al, 2008), and mixed metal oxide sorbent (Tseng et al, 2008;Lou et al, 2009;Chang et al, 2012). As for dechlorination, absorption by Ca-based sorbents has always been a prevalent choice (Yan et al, 2003;Partanen et al, 2005). Others like Na-based sorbents (Nunokawa et al, 2008) and industrial catalysts mixed with multiple components (Dou et al, 2007) were also developed.…”
Section: Introductionmentioning
confidence: 99%